2022
DOI: 10.1177/10439862221096942
|View full text |Cite
|
Sign up to set email alerts
|

Public Perceptions of Police in Fiji

Abstract: Members of the public may have positive, negative, or mixed perceptions of police. Previous research has demonstrated that public perceptions are shaped by their experiences and interactions with police and can influence trust, perceived legitimacy, and future cooperation. Limited research has examined public perceptions of police in small island developing states. This article explores public perceptions of police in Fiji, an island state in the Pacific region. This study employed a mixed-method approach base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…This finding is similar to those found in some of the literature (e.g., Perry & Jonathan-Zamir, 2020;Boon-Kuo et al, 2021;Ghaemmaghami et al, 2021;Heidinger & Cotter, 2020;Nouri & Kochel, 2021;Sargeant et al, 2021;Sibley et al, 2020;Yang et al, 2021). When the public is faced with an emergency or threat, they respond with a general sense of cohesion and positivity (Chand et al, 2022a;Clements, 2020). However, around 12% of participants disagreed and mentioned that they were not satisfied with police performance and suggested some improvements.…”
Section: Overall Public Satisfaction With Police Performancesupporting
confidence: 89%
See 1 more Smart Citation
“…This finding is similar to those found in some of the literature (e.g., Perry & Jonathan-Zamir, 2020;Boon-Kuo et al, 2021;Ghaemmaghami et al, 2021;Heidinger & Cotter, 2020;Nouri & Kochel, 2021;Sargeant et al, 2021;Sibley et al, 2020;Yang et al, 2021). When the public is faced with an emergency or threat, they respond with a general sense of cohesion and positivity (Chand et al, 2022a;Clements, 2020). However, around 12% of participants disagreed and mentioned that they were not satisfied with police performance and suggested some improvements.…”
Section: Overall Public Satisfaction With Police Performancesupporting
confidence: 89%
“…The public's perception of police officers' work during COVID-19 in Fiji was largely positive. This finding of support for the police is a bit surprising because previous research shows little trust in the police (Chand et al, 2022a, Wallace et al, 2022. For example, a study by Wallace et al (2022) in the small islands of Trinidad and Tobago found that public support for police was high during the COVID-19 period when normally public support is low.…”
Section: Summary Of Main Findingsmentioning
confidence: 89%
“…As shown by the research of A. Chand et al (2022), the public's perceptions of police performance are shaped by their experiences and interactions with the police, which can affect trust, perceived legitimacy, and future cooperation between the public and the police in preventing criminal offences.…”
Section: ■ Community Involvement In Policingmentioning
confidence: 99%
“…Similarly, little insight can be drawn from research on the legal socialization process in other SIDS given relatively little attention to the topic. Public perception of police in Pacific Island nations is also generally low (Chand et al, 2022;Howes et al, 2022). In a recent study of community satisfaction with the police in Guam, Howe et al (2022, p. 325) note the importance of "a focus on procedural justice and police performance to contribute to improved community satisfaction with police service provision."…”
Section: Legal Socialization In Caribbean and Other Sidsmentioning
confidence: 99%